The FoxO3 gene and cause‐specific mortality. Issue 4 (13th April 2016) - Willcox, Bradley J.; Tranah, Gregory J.; Chen, Randi; Morris, Brian J.; Masaki, Kamal H.; He, Qimei; Willcox, D. Craig; Allsopp, Richard C.; Moisyadi, Stefan; Poon, Leonard W.; Rodriguez, Beatriz; Newman, Anne B.; et al.
Summary: The G allele of the FOXO3 single nucleotide polymorphism (SNP) rs2802292 exhibits a consistently replicated genetic association with longevity in multiple populations worldwide. The aims of this study were to quantify the mortality risk for the longevity‐associated genotype and to discover the particular cause(s) of death associated with this allele in older Americans of diverse ancestry. It involved a 17‐year prospective cohort study of 3584 older American men of Japanese ancestry from the Honolulu Heart Program cohort, followed by a 17‐year prospective replication study of 1595 white and 1056 black elderly individuals from the Health Aging and Body Composition cohort. The relation between FOXO3 genotype and cause‐specific mortality was ascertained for major causes of death including coronary heart disease (CHD), cancer, and stroke. Age‐adjusted and multivariable Cox proportional hazards models were used to compute hazard ratios (HRs) for all‐cause and cause‐specific mortality. We found G allele carriers had a combined (Japanese, white, and black populations) risk reduction of 10% for total (all‐cause) mortality (HR = 0.90; 95% CI, 0.84–0.95; P  =   0.001). This effect size was consistent across populations and mostly contributed by 26% lower risk for CHD death (HR = 0.74; 95% CI, 0.64–0.86; P  = 0.00004). No other causes of death made a significant contribution to the survival advantage for G allele carriers. In conclusion, at older age, there is a large risk reduction in mortality for G allele carriers, mostly due to lower CHD mortality. The findings support further research on FOXO3 and FoxO3 protein as potential targets for therapeutic intervention in aging‐related diseases, particularly cardiovascular disease.